Activity‐dependent vs. neurotrophic modulation of acetylcholine receptor expression: Evidence from rat soleus and extensor digitorum longus muscles confirms the exclusive role of activity. (26th June 2018) - Buffelli, Mario; Tognana, Enrico; Cangiano, Alberto; Busetto, Giuseppe
Abstract: Evoked electrical muscle activity suppresses the transcription of mRNAs for acetylcholine receptors in extrajunctional myonuclei. Muscle denervation or disuse releases such inhibition and extrajunctional receptors appear. However, in soleus muscles paralysed with nerve‐applied tetrodotoxin, a restricted perijunctional region has been described where myonuclei remain inhibited, a finding attributed to nerve‐derived trophic factor(s). Here, we reinvestigate extrajunctional acetylcholine receptor expression in soleus and extensor digitorum longus muscles up to 90 days after denervation or up to 20 days of disuse, to clarify the role of trophic factors, if any. The perijunctional region of soleus muscles strongly expressed acetylcholine receptors during the first 2–3 weeks of denervation. After 2–3 months, this expression had disappeared. No perijunctional expression was seen after paralysis by tetrodotoxin or botulinum toxin A. In contrast, the extensor digitorum longus never displayed suppressed perijunctional acetylcholine receptor expression after any treatment, suggesting that it is an intrinsic property of soleus muscles. Soleus denervation only transiently removed the suppression, and its presence in long‐term denervated soleus muscles contradicts any contribution from nerve‐derived trophic factor(s). In conclusion, our results confirm that evoked electrical activity is the physiological factor controlling the expression of acetylcholine receptors in the entire extrajunctional membrane of skeletal muscles. Abstract : Muscle activity inhibits extrajunctional acetylcholine receptor (AChR) expression. Denervation/disuse releases the inhibition and extrajunctional AChR appear except near endplates of disused rat soleus muscle (*), a finding attributed to neural trophic factors. With AChR autoradiography, we find the inhibition also in long‐term denervated soleus. Extensor digitorum longus (EDL) muscle never show inhibition, thus being specific of soleus. We confirm activity as the physiologic factor controlling extrajunctional AChR.